ANALISIS PERBANDINGAN ALGORITMA WARSHALL DAN DIJKSTRAA PADA METODE GVRP DALAM PENENTUAN RUTE TERPENDEK (STUDI KASUS : PT YAKULT CABANG SUMBAWA) - Hermanto, Koko (Jurnal TAMBORA, 2021)
Yakult is one of the large industrial companies engaged in the manufacturing sectorfermented milk. This company has business activities, namely selling anddistributing fermented milk to shops. The purpose of this research isanalyze the comparison between Warshall and Dijkstraa's Algorithm on the GVRP method indetermination of the shortest route. The General Vehicle Routing Problem (GVRP) methodused to make it easier to classify the many shops (vertek) intovarious groups (clusters) so as to determine the optimal route and costsminimal. The Warshall algorithm is a method that makes it easy to determinethe shortest route from all points to all points and has a simple method andeasy to implement. While Dijkstraa's algorithm is a method for searchingshortest path between 2 points from starting point to destination point. In this study analyzedthat the Warshall and Dijkstraa algorithms for determining the shortest route have a waycalculations and results that are almost the same as the difference between the total distance of 800 meters withdifference in cost of IDR 645 in one go. The different routes are only in cluster 6 andcluster 9. The conclusion of this study shows that both the Warshall Algorithm andDijkstraa's algorithm has a calculation method that is almost the same as the total distance andcosts have a relatively small difference.